Leukemia Inhibitory Factor Stimulates Primitive Endoderm Expansion in the Bovine Inner Cell Mass - Wooldridge, Lydia K.; Ealy, Alan D. (Frontiers in Animal Science, 2021)
Previous work determined that bovine interleukin-6 (IL6) increases inner cell mass (ICM), primitive endoderm (PE) and total cell number in in vitro produced (IVP) bovine blastocysts. Another IL6 family member, leukemia inhibitory factor (LIF), has the potential to produce the same effects of IL6 due to the presence of its receptor in bovine blastocysts. We compared the abilities of LIF and IL6 to increase ICM cell numbers in day 7, 8 and 9 IVP bovine blastocysts. Supplementation with 100 ng/ml LIF from day 5 onward improved blastocyst formation rates on days 7 and 8 similar to what was observed when supplementing 100 ng/ml IL6. However, LIF supplementation did not cause an increase in ICM numbers like was observed after supplementing IL6. On day 9, increases in PE cell numbers were detected after LIF supplementation, but 300 ng/ml LIF was required to achieve the same effect on PE numbers that was observed by providing 100 ng/ml IL6. Collectively, these results show that LIF can mimic at least some of the effects of IL6 in bovine blastocyst.